Association between the weight-adjusted waist index and age-related macular degeneration in US adults aged≥40 years: the NHANES 2005–2008 - Wu, Yuting; Liu, Yuxin; Jiao, Ziman; Chen, Xin; Li, Haiyu; Zhou, Yunhao; Liu, Guanghui (Frontiers in Medicine, 2025)
ObjectiveThe association between the weight-adjusted waist index (WWI) and age-related macular degeneration (AMD) in US adults aged 40 years and older is unknown. The goal of this study was to ascertain a possible association between the two.MethodsData were obtained from the National Health and Nutrition Examination Survey (NHANES) in the US from 2005 to 2008. The WWI was calculated by dividing waist circumference (WC) by the square root of body weight (kg). AMD was diagnosed based on distinctive features observed in the fundus, using a standard classification system. Weighted logistic regression analyses were conducted to investigate the association between the WWI and AMD. Spline smoothing and threshold effects were applied to explore non-linear correlations. Subgroup analyses were performed to identify underlying covariates affecting this relationship. In addition, receiver operating characteristic (ROC) curve analysis was used to evaluate the predictive power of the WWI for AMD.ResultsA total of 5,132 participants were enrolled in this study. The results showed a significant positive association between the WWI and risk of AMD (OR = 1.76 (1.52, 2.04); p < 0.0001). When the WWI was categorized into tertiles, the highest group exhibited a stronger association compared to the lowest tertile (OR = 2.90 (2.18, 3.86); p < 0.0001) in model 1. The subgroup analyses and interaction tests indicated that the relationship between the WWI and AMD was stable across various populations. The spline smoothing and threshold effects showed a positive non-linear correlation between the WWI and AMD incidence. Furthermore, compared to body mass index (BMI), WC, and weight, the WWI showed better predictability for AMD, as shown by the ROC analysis.ConclusionThere exists a positive non-linear association between the WWI and AMD in US adults aged 40 years and older. The WWI-related obesity management is necessary for the prevention and treatment of AMD.